Potential of Historic Sites for Independence Struggle as Indonesia's Main Tourism Assets in Padang City - YEFTERSON, Ridho Bayu; ANWAR, Syafri; FATIMAH, Siti; SYAFRINA, Yelda; NALDI, Hendra; LIONAR, Uun; PUTRA, Aprizon (Journal of Environmental Management and Tourism; Vol 14 No 8 (2023): JEMT, Volume XIV, Issue 8(72), Winter 2023DO - 10.14505/jemt.v14.8(72).08, 2023)
This research aims to identify the potential of historical sites in Padang City during the physical revolution in building historical awareness in students , and Indonesia's main tourism assets . This study uses qualitative methods from various sources including field observations of historical sites in Padang City. Data processing is carried out by data reduction, namely sorting, and selecting relevant data, presenting data, and drawing conclusions. The results show that historical sites in Padang City have the potential to build historical awareness. Some of these historical sites include the Jong Sumatranen Monument, the Red-White Monument, Joang 45 the Indonesian Youth Information Center (BPPI) Building, the People's Struggle Monument of Gaung, and Simpang Haru Monument/Padang Area Monument. The conclusion of this research is to develop historical awareness. This can be seen from the variety of values that can be developed to help students understand local history, thereby helping to build students' historical awareness starting from their immediate environment.